CHEMICAL CHARACTERISTICS OF SILAGE USE PATIN FISH (Pangasius sp) WITH ADDITION OF FORMIC ACID DURING STORAGE AT ROOM TEMPERATURE - M. Irvansyah, M. Irvansyah; Hasan, Bustari; Irani, Dian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis study aims to determine the chemical characteristics of catfish intestinal silage (pH, NPN, proximate and amino acids) by adding different pH formic acid. The research method used was experimental processing of catfish intestinal silage with the addition of formic acid with different pH. The research data were analyzed using a randomized block design. Test parameters on pH analysis, NPN analysis, proximate analysis (moisture content, ash content, fat content and protein content) and amino acid analysis. Research shows that the intestinal silage of catfish with the addition of formic acid has an effect on the intestinal silage of catfish produced. The use of 1 ml concentration of formic acid during storage for 21 days with characteristics, namely: it has a bright brown appearance, a slightly sour aroma. While the use of 2 ml of formic acid concentration for 21 days of storage with characteristics, namely: it has a dark brown appearance, a slightly sour aroma.Keywords: formic acid, silage, catfish intestines